2020
DOI: 10.1039/d0ra07161g
|View full text |Cite
|
Sign up to set email alerts
|

A brain glioma gene delivery strategy by angiopep-2 and TAT-modified magnetic lipid-polymer hybrid nanoparticles

Abstract: The gene delivery system can penetrate the BBB model efficiently and transfect C6 glioma cells effectively in magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The cells were cultured on the apical side in the Transwell plate (Figure S5A), and TEER measurements were used to monitor the formation of a tight monolayer over 8–10 days, as shown in Figure A. A TEER reading of 50–60 Ω·cm 2 was considered an acceptable value to proceed with the permeability studies around day 8, which is also consistent with previous reports of TEER values in the range of 30–130 Ω·cm 2 . , Figure B shows the transport ratio of the different samples across the formed BBB-mimicking cell monolayers over 24 h. Cubosomes presented a gradual transport and accumulation pattern in the basolateral compartment over time, reaching ∼14 and ∼24% at 24 h for NP and Ang2-NP, respectively. The Ang2 conjugation can increase the penetration of the nanoparticles by up to 10% compared with that of unconjugated NPs.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The cells were cultured on the apical side in the Transwell plate (Figure S5A), and TEER measurements were used to monitor the formation of a tight monolayer over 8–10 days, as shown in Figure A. A TEER reading of 50–60 Ω·cm 2 was considered an acceptable value to proceed with the permeability studies around day 8, which is also consistent with previous reports of TEER values in the range of 30–130 Ω·cm 2 . , Figure B shows the transport ratio of the different samples across the formed BBB-mimicking cell monolayers over 24 h. Cubosomes presented a gradual transport and accumulation pattern in the basolateral compartment over time, reaching ∼14 and ∼24% at 24 h for NP and Ang2-NP, respectively. The Ang2 conjugation can increase the penetration of the nanoparticles by up to 10% compared with that of unconjugated NPs.…”
Section: Resultssupporting
confidence: 83%
“…TEER values of 30–130 Ω·cm 2 for the hCMEC/D3 monolayer are considered an acceptable range to pursue the permeability experiments. , The cells were treated with 25 μg/mL Cyanine 5.5-labeled cubosomes in 500 μL of cell media. At different time points (0, 0.5, 1, 2, 4, 6, and 24 h), 100 μL samples were collected from the basolateral acceptor compartment with the help of fresh cell culture media.…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted that the TEER value was unchanged after different treatments (Figure 2e), further verifying the biocompatibility of the nanosystems. [ 52 ] We also explored the potential influence of protein corona (Figure S5a, Supporting Information). RDMR adsorbed ≈70 µg proteins per mg NPs, which was significantly higher than that of RDM (Figure S5b, c, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacodynamic data revealed that rats in the group with five injections of targeted DNA-bound NPs improved in locomotor activity and apparent recovery of dopaminergic neurons compared to those in other groups [117]. In a proof of principle study, Angiopep-2 and TAT dual modified magnetic lipid-polymer hybrid NPs delivered a reporter gene effectively in C6 cells in a magnetic field [76]. Angiopep-2 NPs have been applied to the delivery of siRNA against genes involved in brain cancer progression and survival.…”
Section: Nucleic Acid Deliverymentioning
confidence: 98%
“…Hence, brain-targeted magnetic NPs are comprised of hybrid materials. These include Angiopep-2 decorated iron gold alloy NPs [75] and magnetic lipid-polymer hybrid NPs [76]. Of great interest is the possibility of utilizing an external magnetic field to promote deposition of the NP at the desired locality and, in this way, modulating the release of the therapeutics [74].…”
Section: Angiopep-2-decorated Nanoparticlesmentioning
confidence: 99%